Tufts sailing team, fall (Tufts Archival Research Center, 2014)
8 x 10 in., photographic print. Front row, from left to right: Mac Cunningham, Manton Scott, Jim Maltman, Ken Hurd, Roger Newberry, Mark Sussman, Glenn Bell. Second row, from left to right: Larry Bell, Don Cundy, Joel Higginson, Sandy Vietor (captain), Lou Libby, Ken Tye, George Class. Third row, from left to right: Chris Pollack, Geoff Clayton, George Norton, Andy Fortunka, Rich Marchand, Charlie Simpson, Joe Duplin (coach). Fall 1971 Tufts University sailing team was rated number 1 in the United States by "Soundings" magazine.